A Licensing Advice for Small Micro Businesses in Ciomas Village, Ciawigebang District, Kuningan Regency - Dede Djuniardi; Dikdik Harjadi; Lili Karmela F.; Aini Nursafaah (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Following the Covid 19 outbreak, Micro, Small, and Medium Enterprises in Kuningan Regency are working to establish themselves and create well-known products. However, there is still a lack of knowledge on licensing issues, including BINs and MSME Business Permits. MSMEs must also be familiar with various licenses, including those from the Home Industry Food (PIRT), Drug and Food Control Agency (BPOM), Halal Products (BPJPH), and Intellectual Property Rights (HAKI). The preliminary survey's findings demonstrate that MSME actors in Ciomas village still do not comprehend the significance of permits for their companies. By demonstrating the significance of permits—particularly Business Identification Numbers and Small and Medium Enterprise Permits—as well as a number of other types of permits required by MSME actors in Ciomas Village, Ciawigebang District, Kuningan Regency, these issues will be resolved. Starting with socialization on the value of licensing and the licensing procedure at the approved agency or institution, the counseling approach is applied. 30 MSMEs in Ciomas Village are expected to comprehend various kinds of business licenses as a result of this training, which is the goal.